2020
DOI: 10.1186/s13071-020-3973-y
|View full text |Cite
|
Sign up to set email alerts
|

Ticks and associated pathogens in camels (Camelus dromedarius) from Riyadh Province, Saudi Arabia

Abstract: Background: Camel production in Saudi Arabia is severely affected by various diseases and by inadequate veterinary services. Ticks and tick-borne pathogens (TBPs) affect the health and wellbeing of camels consequently diminishing their productivity and performances. In addition, camels may act as hosts for TBPs (e.g. Anaplasma phagocytophilum) causing diseases in humans. The current study aimed to determine the prevalence of ixodid ticks and molecularly investigate the associated pathogens in camels from Saudi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 57 publications
3
43
1
Order By: Relevance
“…All of the 74 dogs tested from Riyadh province were negativeforall testedpathogens, while 45 previously been recorded in dogs from Qatar [30] and Iran [35].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…All of the 74 dogs tested from Riyadh province were negativeforall testedpathogens, while 45 previously been recorded in dogs from Qatar [30] and Iran [35].…”
Section: Resultsmentioning
confidence: 87%
“…sanguineus has been reported in low prevalence in domestic and wild animals including dogs and cats fromcentral parts of Saudi Arabia [6,39,40], along with western and southern Saudi Arabia [41,42,43]. The climate of Saudi Arabia has shown to be potentially suitable to the perpetuation of vectors and transmission of several arthropod-borne diseases [44,45]. Indeed the environmental conditions of Saudi Arabia aresuitablefor the development of different tick species due to wide range of climatic conditions [46].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many studies have used molecular tools to screen and identify these pathogens worldwide in camel hosts and their tick vectors (Mazyad and Khalaf, 2002;Sloboda et al, 2011;Qablan et al, 2012;Belkahia et al, 2015;Khamesipour et al, 2015;Li et al, 2015;Lorusso et al, 2016;Ait Lbacha et al, 2017;Alsarraf et al, 2017;Sharifiyazdi et al, 2017;Azmat et al, 2018;Bahrami et al, 2018;Noaman, 2018;Azeem et al, 2019;Sazmand et al, 2019;Selmi et al, 2019;Selmi et al, 2020). In Saudi Arabia, very few studies concerned with these pathogens in camels have been performed (Al-Khalifa et al, 2009;Ghafar and Shobrak, 2014;Mostafa and Dajem, 2014;Bastos et al, 2015;Alanazi et al, 2018;Alanazi et al, 2020). Al-Khalifa et al (2009) found that camels in the Asir region were free from blood parasites.…”
Section: Discussionmentioning
confidence: 99%
“…DNA. Alanazi et al (2020) reported several pathogens (e.g. Anaplasma platys, Anaplasma phagocytophilum, Anaplasma sp., Ehrlichia canis and Hepatozoon canis) in camels from Riyadh Province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation